AB0181 Epidemiology study about osteoporosis in postmenopausal women about 1000 case. (1st June 2001) - Quennesson, S; Quennesson, E; Preux, PM; Di Fazano, C Scotto; Coyral, D; Vergne, P; Bonnet, C; Bertin, P; Treves, R
Abstract : Background: Osteoporosis is a bone disease who concerns above all postmenopausal women. It's characterised by bone loss and associated fractures. In France, in 1995 it's 1% hospital cost. We realised a transversal study about osteoporosis and risk factors with 1000 women. Objectives: We excluded women with hormonal substitutive treatment and secondary osteoporosis. The study group was randomised. All patients were interviewed about risk factor and bone mineral density was measured by dual energy X ray. One woman was excluded for myeloma. Methods: We compared risk factor between osteoporosis group and non osteoporosis group determined by densitometry OMS criteria, with student t test or chi2. Finally a multivarious analysis includes all significative risk factor.(p < 0, 05). Results: In our study, there was 25%osteoporotic patients. The univarious analysis find a significant relation between osteoporosis and study level, the age at menopause, thyroid disease, body mass index, calcium intake, milk drink, fresh water consumption, white cheese. The multivarious analysis shows a significant relation between osteoporosis and age (odds ratio = 1, 1 per year), the level study (odds ratio = 0, 34 between; after first grade diploma and no education), Body Mass Index (odds ratio = 0, 86 per unity), milk drinks (odds ratio = 0, 7). The discriminant analysis after further adjustment for confounding factors allows to diagnose 67% of osteoporotic women. Conclusion: In our population, we find some usual risk factor of literature. The interview is not sufficient to diagnose osteoporosis certainly but allow to purpose bone density. The results of this bone density with clinical information is necessary to start the best treatment.